2021
DOI: 10.1002/ejoc.202101046
|View full text |Cite
|
Sign up to set email alerts
|

FeCl3‐Catalyzed Formal [3+2] Cyclodimerization of 4‐Carbonyl‐1,2‐diaza‐1,3‐dienes

Abstract: Substituted 1‐aminopyrroles are easily accessible by iron‐catalyzed cascade reaction of 1,2‐diaza‐1,3‐dienes. Mechanistically, a formal [3+2] cyclodimerization is hypothesized to proceed through a [4+2] cyclodimerization of 4‐substitued 1,2‐diaza‐1,3‐dienes followed by intramolecular ring closure to fused diaziridin‐pyrrolines which is successively opened to undergo a ring contraction process and consequently generate the desired pyrrole moiety. The presence of activated hydrogen in the terminal position of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…Similarly to what was observed by Yu and co-workers for the intramolecular cyclization of alkynyl aldehyde acetals [ 28 29 ], it was found that the use of FeCl 3 provided the better result in terms of overall yield (entry 3, Table 1 ). Moreover, the choice of iron(III) seemed to have remarkable advantages such as an environmentally benign alternative to traditional transition-metal catalysis, a low cost, nontoxicity, good stability, and easy handling [ 30 31 ]. Upon increasing the amount of FeCl 3 to 20 mol %, the time of the reaction was reduced from 86 to 38 hours, and the yield of 5a was incremented with respect to 6a (entry 4, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to what was observed by Yu and co-workers for the intramolecular cyclization of alkynyl aldehyde acetals [ 28 29 ], it was found that the use of FeCl 3 provided the better result in terms of overall yield (entry 3, Table 1 ). Moreover, the choice of iron(III) seemed to have remarkable advantages such as an environmentally benign alternative to traditional transition-metal catalysis, a low cost, nontoxicity, good stability, and easy handling [ 30 31 ]. Upon increasing the amount of FeCl 3 to 20 mol %, the time of the reaction was reduced from 86 to 38 hours, and the yield of 5a was incremented with respect to 6a (entry 4, Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclodimerization of 1,2-diaza-1,3-dienes 57 catalyzed for FeCl 3 generates a series of fully substituted symmetrical 1-aminopyrroles 58 [ 40 ]. The reaction begins with [4+2] Aza-Diels–Alder cycloaddition to produce diazenyl-tetrahydropyridazine-3,4-dicarboxylates 59 that lose N 2 and R 1 CO 2 H to yield the intermediate 60 .…”
Section: Synthesis Of Heterocycles From 12-diaza-13-dienesmentioning
confidence: 99%